Sistem Informasi Geografis Analisis Penggunaan Air Bersih dan Sebaran Kasus Stunting di Kabupaten Jepara Tahun 2023 - Laras Wulansari; Bambang Agus Herlambang; Ahmad Khoirul Anam (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study examines the relationship between the number of people in an area, the distribution of clean water access, and the number of stunting cases in Jepara Regency in 2023. The method used is quantitative descriptive using the Geographic Information System and data from the Jepara Regency Central Statistics Agency in 2024 and the Indonesian One Data Portal from the Ministry of National Development Planning/Bappenas in 2023. The analysis was carried out by creating a thematic map divided into low, medium, and high categories. The results of the study showed 1482 cases of stunting in children under five. Jepara District is recorded as having the largest population of 3184 people per km² with good access to clean water of 18665 customers and as much as 306165 m³, but stunting cases there are relatively low where as many as 51 cases were found. Meanwhile, Keling District, with a small population of 562 people per km² and limited access to clean water, with 503 customers and 7667 m³ of clean water distributed, had the highest number of stunting cases, at 265. Karimunjawa District, an archipelago with low population density and water access, also recorded moderate stunting cases, with 27 cases. This analysis concludes that population size does not always correlate with stunting rates. Conversely, adequate access to clean water significantly reduces the risk of stunting. Furthermore, the use of Geographic Information Systems has proven effective in identifying inequalities between districts. This can assist in planning stunting prevention measures in coastal areas of Jepara.